An alternative history of Lusophone Anthropology - Ramos, M. (Seminar on History of Anthropology - Institut fuer Ethnologie - Universitat Hamburg, 13 June 2017, 2017)
Is anthropology as produced in Portugal worth the title of social science? A historical review of the lack of scientific debate and of the systematic censorship of divergent ideas makes it clear that it isn't. The history of anthropology produced in Portugal is a sad story of a small corporative enclave immersed in mediocrity